Histological aspects of skeletal muscle fibers splitting of C57BL/6NCrl mice - Makovický, P; Makovický, P (Physiological research, 2020)
The objective of the current study is to present data on the splitting of skeletal muscle fibers in C57BL/6NCrl mice. Skeletal muscles (m. rectus femoris (m. quadriceps femoris)) from 500 (250 female and 250 male) C57BL/6NCrl mice in the 16th week of life were sampled during autopsy and afterwards standardly histologically processed. Results show spontaneous skeletal muscle fiber splitting which is followed by skeletal muscle fiber regeneration. One solitary skeletal muscle fiber is split, or is in contact with few localized splitting skeletal muscle fibers. Part of the split skeletal muscular fiber is phagocytosed, but the remaining skeletal muscular fiber splits are merged into one regenerating skeletal muscle fiber. Nuclei move from the periphery to the regenerating skeletal muscle fiber center during this process. No differences were observed between female and male mice and the morphometry results document < 1 % skeletal muscle fiber splitting. If skeletal muscular fibers splitting occurs 5 % > of all skeletal muscular fibers, it is suggested to describe and calculate this in the final histopathological report.
Keywords: Mice; kosterní svalová vlákna; Female; Muscle Fibers, Skeletal; Animals; ženské pohlaví; mužské pohlaví; Male; zvířata; Mice, Inbred C57BL; myši; myši inbrední C57BL